2022
DOI: 10.3390/biomedicines10123245
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adenomyosis on Infertile Patients—Therapy Options and Reproductive Outcomes

Abstract: Adenomyosis is associated with a negative impact on reproductive outcomes. Although adenomyosis is detected more frequently in women of late reproductive age, its impact on pregnancy rates is important because, in today’s world, family planning has shifted towards the late reproductive phase of life for many women. Although the diagnostic indications for imaging studies are well-known, we lack strict diagnostic criteria and classification systems concerning the extent of the disease. Selecting the optimal evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Among the anatomical alterations, we can include uterine enlargement, the presence of intramural adenomyomas that may distort the uterine cavity, anomalies in utero‐tubal transport and impairment of contractility and spermatozoic migration, functional endometrial disturbance, and malformation of the junctional zone 22 . At the microscopic level can be seen myocytic and nuclear hypertrophy, morphological abnormalities in cells and mitochondria, as well as disruptions in the Ca 2+ cycle, leading to muscular dyskinesia 23 . Maubon et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the anatomical alterations, we can include uterine enlargement, the presence of intramural adenomyomas that may distort the uterine cavity, anomalies in utero‐tubal transport and impairment of contractility and spermatozoic migration, functional endometrial disturbance, and malformation of the junctional zone 22 . At the microscopic level can be seen myocytic and nuclear hypertrophy, morphological abnormalities in cells and mitochondria, as well as disruptions in the Ca 2+ cycle, leading to muscular dyskinesia 23 . Maubon et al.…”
Section: Methodsmentioning
confidence: 99%
“…22 At the microscopic level can be seen myocytic and nuclear hypertrophy, morphological abnormalities in cells and mitochondria, as well as disruptions in the Ca 2+ cycle, leading to muscular dyskinesia . 23 Maubon et al showed that a junctional zone (JZ) bigger than 7 mm was correlated to a higher implantation failure; 24 taking into consideration the myometrial wall, a thickness of more than 2.5 cm on TVUS seems to have an increasingly adverse effect on IVF/intracytoplasmic sperm injection (ICSI). 25 The pathological alteration of the consistency of the myometrium, along with myocyte dyskinesia, distorts the balance of intracellular calcium concentrations with repercussions such as disturbed contractility and consequent hindrances to sperm migration.…”
Section: Adenomyosis (In)fertility and Pregnancy Outcomesmentioning
confidence: 99%
“…Possible mechanisms through which adenomyosis causes impairment of implantation have been described in the recent literature, including anatomical distortion of the uterine cavity, disturbed uterine peristalsis and sperm transport, dysfunctional hyperperistalsis of the inner myometrium, increased intrauterine pressure, a disturbance in normal myocyte contractility with a subsequent loss of normal rhythmic contraction, altered sex steroid hormone pathways, increased inflammatory markers and oxidative stress, the reduced expression of implantation markers, a lack of expression of adhesion molecules, and altered function of the gene for embryonic development (the HOXA 10 gene) [14]. Different locations in the female genital tract and the negative impact of adenomyosis on the individual steps of reproduction are shown in Figure 2 [45]. Other suggested mechanisms are focused on P450 (P450arom) and mRNA expression, which seem to be present in women with adenomyosis, leading to lower clinical pregnancy rates [46].…”
Section: Effect Of Adenomyosis On Fertilitymentioning
confidence: 99%